ENGARUH SOSIALISASI KELUARGA TERHADAP PERKEMBANGAN PRILAKU ANAK (Studi Kasus: Jorong Lubuak Aluang Kecamatan Ampek Nagari Kabupaten Agam) - Warni, Cinto; Melia, Yenni; Elvawati, Elvawati (Pendidikan Sosiologi, 2013)
FamilyÂ isÂ theÂ firstÂ socializationÂ agentÂ inÂ society,Â becauseÂ theÂ firstÂ time childÂ knowsÂ aboutÂ valueÂ andÂ norm.Â TheÂ parentÂ isÂ anÂ essentialÂ roleÂ inÂ formative childÂ behaviorÂ developing.Â TheÂ processÂ socializationÂ thatÂ doesnâtÂ byÂ parentsÂ is communicationÂ andÂ attention.Â InÂ thisÂ researchÂ analyzedÂ theÂ effectÂ ofÂ family socializationÂ inÂ childÂ behaviorÂ developingÂ inÂ JorongÂ LubuakÂ aluang.Â InÂ the background of this research there is some of family that doesnât liabilities as first socializationÂ agent.Â OneÂ ofÂ themÂ onlyÂ thinksÂ aboutÂ theirÂ privateÂ withoutÂ think about their child. Thus, it can give effect of child behavior. The formulation of the problemÂ âDoesÂ familyÂ socializationÂ giveÂ significantÂ effectÂ inÂ childÂ behavior developingâ.Â TheÂ purposeÂ ofÂ thisÂ researchÂ isÂ toÂ describeÂ familyÂ socialization influence to child behavior developing.The theory that is utilized in this research is functional Structural (TalcotPerson).Â Â ObservationalÂ methodÂ thatÂ isÂ utilizedÂ isÂ quantitativeÂ methodÂ with descriptiveÂ approaching.Â DataÂ collectingÂ toolÂ asÂ questionnaire.Â ThisÂ researchÂ is done to 50 informen, with aim to describe family socialization influence to child behavior developing in Jorong Lubuak Aluang.Â ThisÂ informen consistÂ ofÂ 50Â childwith age 10 until 12 years old that is explain through questionnaire. From the research results show that: 1) The parentâs communication with their child is adverse because of 50 person respondent 62 % adverse categories. 2) The parentâs attention with their child is adverse because of 50 person respondent 72 % adverse categories. 3) The family socialization adverse in child behavior of 50Â personÂ respondentÂ 54Â adverseÂ categories.Â 4)Â ChildÂ behaviorÂ CausesÂ justÂ fine looked of 50 respondent 60% just fine categories. Based on the result research, thereÂ isÂ familyÂ socializationÂ influenceÂ toÂ childÂ behaviorÂ developingÂ inÂ Jorong Lubuak Aluang. It visually of 50 respondents 62% for adverse.